VvVHP1; 2 Is Transcriptionally Activated by VvMYBA1 and Promotes Anthocyanin Accumulation of Grape Berry Skins via Glucose Signal - Sun, Tianyu; Xu, Lili; Sun, Hong; Yue, Qianyu; Zhai, Heng; Yao, Yuxin (Frontiers in Plant Science, 2017)
In this work, four vacuolar H+-PPase (VHP) genes were identified in the grape genome. Among them, VvVHP1;2 was strongly expressed in berry skin and its expression exhibited high correlations to anthocyanin content of berry skin during berry ripening and under ABA and UVB treatments. VvVHP1;2 was transcriptionally activated directly by VvMYBA1, and VvVHP1;2 overexpression promoted anthocyanin accumulation in berry skins and Arabidopsis leaves; therefore, VvVHP1;2 mediated VvMYBA1-regulated berry pigmentation. On the other hand, RNA-Seq analysis of WT and transgenic berry skins revealed that carbohydrate metabolism, flavonoid metabolism and regulation and solute carrier family expression were the most clearly altered biological processes. Further experiments elucidated that VvVHP1;2 overexpression up-regulated the expression of the genes related to anthocyanin biosynthesis and transport via hexokinase-mediated glucose signal and thereby promoted anthocyanin accumulation in berry skins and Arabidopsis leaves. Additionally, modifications of sugar status caused by enhanced hexokinase activities likely play a key role in VvVHP1;2-induced sugar signaling.